D9.6 Report social media activity - Papoutsa, Christiana; Loulli, Eleni (My University, 2022)
This deliverable provides an overview of all social media activity for the EXCELSIOR H2020 Teaming Project. In addition, it includes the communication material published in social media. The deliverable provides an analysis of the demographics of the social media activities by platform. To date, the EXCELSIOR project has received a positive response on several social media platforms.
Keywords: Remote Sensing; EXCELSIOR; ERATOSTHENES Centre of Excellence; Earth Observation